Electrocatalysts for Oxygen/Hydrogen-Involved Reactions (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue contains some recently experimental and theoretical advances in hydrogen evolution reaction, oxygen evolution reaction, and oxygen reduction reaction, and the applications in water splitting, proton exchange membrane fuel cells, and lithium-ion batteries.